Do governance indicators have a role in remittances-growth nexus in Egypt? - Alamoudi, Abdulrhman (Economic Journal of Emerging Markets, 2024)
Purpose ― Drawing on annual data from 1996 to 2022, this study aims to examine the effect of Egypt’s real GDP growth. Methods ― Autoregressive Distributed Lag (ARDL) and Cointegration technique are applied by first examining the stationarity of the series by utilizing the Augmented-Dicky-Fuller (ADF) unit root test. The bound cointegration test is then implemented to evaluate the existence of cointegration among the variables. Findings ― The results indicate that the GDP growth rate has a long-run positive relationship with remittance inflows in Egypt. This paper also finds that the average governance indicators in Egypt, which include government effectiveness, political stability, control of corruption and regulatory quality, voice and accountability, and the rule of law, could help facilitate the long-run effect of remittances on GDP growth. Implication ― The findings imply that maintaining high levels of governance indicators is essential for helping Egypt benefit from remittances and enhancing its economic growth.Originality/value ― The study is a pioneer in including the average governance indicators in the remittance-growth nexus study for Egypt. Its purpose is to assess whether governance quality affects the nexus and whether there exists a threshold for the average governance indicators below which the flow of remittances does not encourage economic growth.